Implementation of Non-Cash Food Assistance Policy in Karangmulya Village, Kadungora Sub-District, Garut District - Puji Lestari (GoResearch - Research & Publishing House, 2025)
The implementation of the Non-Cash Food Assistance Program (BPNT) in Karangmulya Village, Kadungora District, Garut Regency, still faces several challenges that hinder its overall effectiveness. One major problem is the lack of coordination between implementing officers and Beneficiary Families (KPM), which leads to an increase in the number of recipients each year without proper verification. Furthermore, some officers do not fully understand their responsibilities in managing the program, resulting in frequent errors in targeting assistance. This study aims to analyze how BPNT is implemented at the village level. This study uses a descriptive qualitative approach with George C. Edward III's implementation theory (in Subarsono, 2011: 90–92) as its analytical tool, focusing on four indicators: communication, resources, disposition, and bureaucratic structure. Data were collected through observation, interviews with relevant stakeholders, and documentation. The findings indicate that implementation in Karangmulya Village is not optimal and remains inconsistent with the established policy objectives. Many residents still do not know how to access or benefit from this program. Therefore, systematic and widespread community outreach is urgently needed. Through consistent outreach and interagency coordination, the village government can gradually improve program understanding, targeting accuracy, and overall service delivery.